Decision Making for Management of Periimplant Diseases. Issue 3 (June 2018) - Sinjab, Khaled; Garaicoa-Pazmino, Carlos; Wang, Hom-Lay
Abstract : Introduction: Nonsurgical and surgical management of periimplant mucositis and periimplantitis have shown promising results in arresting periimplant marginal bone loss (MBL) and preventing implant loss. However, management of periimplant diseases still remains unpredictable for full reconstruction of lost tissues and completely arrests disease progression. The present study proposes a decision tree that compiles both clinical and radiographic presentation of failing implants to aid in the decision making for their management. Materials and Methods: An extensive literature review was performed using 3 electronic databases (PubMed, Ovid MEDLINE, and Cochrane Central) on the most recent treatment modalities for the management of periimplant diseases. Discussion: Evidence-based treatment suggestions were primarily derived from periimplant defect morphology, presence, and severity of periimplant MBL. More evidence is required supporting soft-tissue augmentation for the treatment of periimplant diseases. Conclusion: Management of periimplant diseases can include lasers, mechanical instrumentation, chemical detoxification, and antimicrobial agents for nonsurgical approaches. On the other hand, removal of failing implants, resective surgery, guided bone regeneration, and soft-tissue grafting are presented as valid options for the surgical treatment of periimplantitis.